Teacher Competency in Civic Education Learning to Encounter Industrial Revolution 4.0 (Case Study at Sekolah Menengah Pertama 2 Bandung) - Faris Mu’taz Fawwazi; Aim Abdulkarim; Kokom Komalasari (AIBPM Publisher, 2020)
The industrial revolution has had a profound effect on the world of education. In addition to having a positive impact on several things, the industrial revolution also had a negative effect. The method used in this research is a case study with a qualitative approach, which will be applied in schools. The results of this study indicate: How does the Pendidikan Kewarganegaraan teacher's competence develop content, processes, media, learning resources and assessment of the learning process in the industrial revolution 4.0? After doing research, the industrial revolution provides a change in terms of learning media to learning in the classroom conducted by teachers, through the industrial revolution 4.0, teachers are increasingly motivated to develop learning activities in the classroom and also increasingly diverse learning media.